Redescription of two West Himalayan Cheiracanthium (Aranei: Cheiracanthiidae) - Marusik Yu.M.; Omelko M.M.; Simmons Z.M. (KMK Scientific Press, 2022)
Two species of Cheiracanthium, known only from the original descriptions, C. adjacens O. Pickard-Cambridge, 1885 and C. approximatum O. Pickard-Cambridge, 1885, are redescribed based on their types. A lectotype is designated for C. adjacens. The type localities of the two species lie in Himalaya, not in Tibet (Yarkand, Xinjiang, China), as indicated in catalogs. The lectotype (designated here) of C. insulanum (Thorell, 1878) a species described from Ambon, Indonesia is illustrated for the first time. It was found that literature records and figures of C. insulanum refer to C. approximatum. Because of this, seven species considered as junior synonyms of C. insulanum are moved to synonyms of C. approximatum: C. adjacensoides Song, Chen et Hou, 1990, syn.n., C. paradjacens Chen et Gao, 1990, syn.n., C. payateus Barrion et Litsinger, 1995, syn.n., C. tigbauaensis Barrion et Litsinger, 1995, syn.n., C. tingilium Barrion et Litsinger, 1995, syn.n., C. bikakapenalcolium Barrion et Litsinger, 1995, syn.n. and Cheiracanthium hugiscium Barrion et Litsinger, 1995, syn.n.